Global Warming dan Carbon Trading Perspektif Fiqh - Abdul Jalil (AL-TAHRIR, 2012)
Developed countries have contributed global emissions about 70%. They made Clean Development Mechanism (CDM) program as consequence of their responsibility. This program used Certified Emission Reduction (CER) mechanism as evidence of payment claim. With CER, efforts to reduce carbon emissions has been turned into a business that has environmental insight. This paper discusses those issues in fiqih perspective having purpose to establish cultural awareness about what and how the global warming and the carbon trading are. In one hand, this perspective will be more showed up when the carbon trading program is activated and requires mass mobilization to carry it out. This paper concluded that ratifying Kyoto’s protocol in fiqih view is a duty that must be obeyed by every person as an effort to eliminate the mad}arat for mankind. Diverting responsibility to decrease the global warming is categorized as akad ijarah so that the actor has gotten compensation (‘iwadh). The money from carbon sale done by the trader is legally belong to him and categorized into ma>l zakawi> which its alms must be distributed.